Problems and needs in developing a program to enhance financial literacy for pre-service teachers - Sawettaporn Tangwancharoen; Piyaphat Nithitakkharanon (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
Financial literacy is increasingly vital in today’s complex economic context, pre-service teachers often lack the necessary skills to manage personal finances effectively. This study aimed to (1) examine the problems in developing programs to promote financial literacy among pre-service teachers, (2) identify the need for such programs, and (3) analyze the key components of financial literacy relevant to this group. A mixed-method approach was employed, combining qualitative interviews with financial experts and education professionals with quantitative surveys administered to pre-service teachers. Findings revealed significant gaps in financial management, particularly in budgeting, debt management, and saving strategies. Expert insights highlighted three problematic factors: insufficient financial literacy, undisciplined financial behavior, and inappropriate financial attitudes. The majority of participants were female (86.33%), aged around 20 years, with limited incomes (3,000–5,999 baht monthly) and high dependence on the Education Loan Fund (87.67%). The study identified financial knowledge, financial behavior, and financial attitudes as the core components for effective program design. Results emphasize the urgent need for structured, context-specific financial literacy curricula within teacher education programs, focusing on debt management, disciplined budgeting, and long-term financial planning. These findings provide a foundation for evidence-based interventions that can strengthen the financial capabilities for pre-service teachers.